Across system comparative assessment of irrigation performance of community managed scheme in Southern Ethiopia - Bantero, B.; Ayana, M.; Awulachew, Seleshi Bekele (2008)
The water users located at the upstream of the irrigation system have more access to water than those located at the downstream of the system. Moreover, the irrigation activity of tail-enders is seriously affected in both water scarce and water abundant periods due to under and over irrigation respectively. Not only water but also the situation of landholding affects the productivity and income of the farming community. The goal of this study was to assess the spatial variation of irrigation performance and to evaluate its effects in terms of performance of agricultural production (intensification and productivity), income and resources base as well as the environment. Across-system performance assessment study sponsored by International Water Management Institute (IWMI) was done on the basis of simple illustration of the approach followed for the assessment and different levels of water accessibility along the canal reaches. The level of availability of irrigation water or accessibility to the farm is affected by the proximity of the farm to the water source or to the water carrying canals. The study confirmed that as one gets away from both the water source and the canal the accessibility of water becomes less and less, unless proper system for water allocation is in place and practiced. In view of that, six zones can be differentiated based on the condition of water accessibility. These are highly accessible, moderately accessible, less accessible, very less accessible, poorly accessible and water scarce zones. Sometimes the tail-end, which is characterized by water scarce zone, is also found to be affected by water logging. Since, available water and demand for water are not continuously monitored and managed, the situation outlined paves the path for potential conflicts among water users in response to visible livelihood differences. Despite disruption of downstream users from irrigating their field, significant loss of scarce resource by the upstream users have resulted in detectable environmental threat such as water logging, sodicity (10.44meq/l, k (H.C.) 0.00279cm/hr) and salinity problems in the area.